(untitled) (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2021)
The purpose of this paper was to make meaning of doctoral students’ experiences as they expanded their understanding of teaching and learning through reflection. Using case study as a methodology approach, a group of doctoral candidates examined purposeful events that unfolded during their participation in an international doctoral forum in East Asia. Guided by transformative learning theory and reflective practice inquiry, the research findings indicated that graduate students’ perceptions of teaching and learning in an international context were shaped by their various identities, past experiences, cultural backgrounds, and social interactions. The research also illustrated how participation in the forum supported doctoral candidates in advancing their scholarly identities as they reflected upon various moments throughout the event. The implications for the Scholarship of Teaching and Learning (SoTL) were significant as reflective activities surrounding the doctoral forum helped to explain how transformative learning experiences could contribute to doctoral students’ transition into academia.